Induction of superovulation using inhibin antiserum and competence of embryo development in wild large Japanese field mice (Apodemus speciosus). Issue 12 (20th October 2019) - Meguro, Kanna; Komatsu, Kazuki; Ohdaira, Takuya; Nakagata, Naomi; Nakata, Akifumi; Fukumoto, Manabu; Miura, Tomisato; Yamashiro, Hideaki
Abstract: Seasonally, bred wild mice provide a unique bioresource, with high genetic diversity that differs from wild‐derived mice and laboratory mice. This study aimed to establish an alternative superovulation method using wild large Japanese field mice ( Apodemus speciosus ) as the model species. Specifically, we investigated how the application of inhibin antiserum and equine chorionic gonadotropin (IASe) during both the reproductive and non‐reproductive seasons impact the ovulation rate and competence of embryo development after in vitro fertilization (IVF) with fresh and cryopreserved sperm. When the wild mice were superovulated by injecting eCG followed by human chorionic gonadotropin (hCG), few oocytes were collected during the reproductive and non‐reproductive seasons. In comparison, the number of ovulated oocytes was dramatically enhanced by the administration of IASe, followed by isolation of ovulated oocytes 24 hr after 30 IU hCG administration. The IVF oocytes that were in vitro cultured (IVC) with medium containing serum further developed to the 2‐ and/or 4‐cell stage using both fresh and frozen‐thawed sperm. In conclusion, we successfully established an alternative protocol for collecting ovulated oocytes from wild large Japanese field mice by administering IASe and hCG during both the reproductive and non‐reproductive seasons. This study is the first to develop IVF–IVC wild large Japanese field mice beyond the 2‐ and/or 4‐cell stage in vitro using fresh and cryopreserved sperm. This approach could be used in other species of wild or endangered mice to reduce the number of animals used for experiments, or in maintaining stocks of germ cells or embryos.